Kebijakan Pengaturan Pencegahan Stunting Ditinjau Dari Ketentuan Hukum Perkawinan - Ni Wayan Eka Sumartini (Satya Dharma : Jurnal Ilmu Hukum, 2022)
Disrupted growth and development of children can be caused by various factors. Continuous growth and development disorders can cause stunting so that it affects various things in a child's life, including the child's future. Children need optimal support from parents and their environment to grow and develop properly so that they will produce a reliable future generation. This paper aims to determine the role of the family in reducing the number of children with stunting from the perspective of marriage law. The government seeks to reduce the stunting rate through setting the age limit for marriage. The literature study method was used in the preparation of this paper. Based on the results of the study, it was found that the role of the family in reducing and preventing the incidence of stunting in children. The responsibility for caring for and caring for children is the duty of parents and the surrounding environment.